2016
DOI: 10.1080/19393210.2016.1216468
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillusand aflatoxin in groundnut (Arachis hypogaeaL.) and groundnut cake in Eastern Ethiopia

Abstract: This study was conducted to assess major Aspergillus species and aflatoxins associated with groundnut seeds and cake in Eastern Ethiopia and evaluate growers' management practices. A total of 160 groundnut seed samples from farmers' stores and 50 groundnut cake samples from cafe and restaurants were collected. Fungal isolation was done from groundnut seed samples. Aspergillus flavus was the dominant species followed by Aspergillus parasiticus. Aflatoxin analyses of groundnut seed samples were performed using u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 24 publications
0
26
2
Order By: Relevance
“…In the second year (2015), the highest aflatoxin B 1 (5704.4 µg/kg) and B 2 (2219.0 µg/kg) were detected in samples harvested from the control plots. Recently Mohammed et al (2016) detected aflatoxin B 1 2526.3 µg/kg in groundnut seed collected from growers' storages. These results indicated that, the groundnut seed produced in eastern Ethiopia was badly contaminated with aflatoxin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the second year (2015), the highest aflatoxin B 1 (5704.4 µg/kg) and B 2 (2219.0 µg/kg) were detected in samples harvested from the control plots. Recently Mohammed et al (2016) detected aflatoxin B 1 2526.3 µg/kg in groundnut seed collected from growers' storages. These results indicated that, the groundnut seed produced in eastern Ethiopia was badly contaminated with aflatoxin.…”
Section: Discussionmentioning
confidence: 99%
“…A pre-pleated filter paper Whatman No. 4 was inserted in the mixture, 500 μL of filtrate was transferred to a disposable glass test tube followed by addition of 500 μL of acetonitrile to the same tubes and mixed thoroughly (Mohammed et al, 2016). Then, 500 μL of the mixture was pipetted into the 1.5-mL columns prepared for cleaning.…”
Section: Aflatoxin Analysis From Groundnut Seedmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, these markers differentiated groups within the toxigenic A. flavus group (GIII) and showed some association with the amount of aflatoxin produced. Although higher concentration of aflatoxin are expected from S strains (Horn and Dorner 1999), in the year 2014 only L strains were observed in the dilutions plated; using the same sampling protocol, we usually recover L and S strains from other geographical areas (Mohammed et al 2016). Since point mutations (Ehrlich and Cotty 2004) or small deletions (Calvo et al 2004) in regulatory genes are sufficient to affect aflatoxin production, further studies should be conducted to determine if the insertions/deletions observed are related to the capability to produce large or small amounts of aflatoxins.…”
Section: Discussionmentioning
confidence: 99%